Ecological Characteristics and Community Utilisation of Mangrove Ecosystems in West Biak, Central Papua, Indonesia - Likumahua, Engly Sisilya; Boli, Paulus; Pattiasina, Selfinus; Pattiasina, Thomas Frans; Purba, Gandi Yantri Sevantina (Biotropika: Journal of Tropical Biology, 2026)
Mangrove ecosystems are increasingly threatened by human activities, such as tree cutting, waste disposal, and land conversion for various purposes. Similar pressures occur in the coastal region of West Biak, Papua, Indonesia. This study aimed to analyse the ecological condition of mangrove ecosystems and to identify community activities related to mangrove utilisation. The research was conducted over a three-month period, from March to May 2024, in Sopendo and Mamoribo Villages, West Biak District, Biak Numfor Regency, covering a total area of 52.91 ha. Mangrove vegetation data were collected using line transects and quadrat plots, while information on community activities was obtained through interviews and questionnaires. Mangrove vegetation structure was analysed using the Importance Value Index (IVI) while species diversity was assessed using the Shannon–Wiener Diversity Index. Interview data were analysed descriptively to identify patterns of community utilisation of mangrove resources. A total of twelve mangrove species were identified. Rhizophora apiculata showed the highest IVI values, reaching 85.66 in Mamoribo and 105.08 in Sopendo, indicating its strong dominance within the mangrove community structure. The ecological condition of the mangrove ecosystem is closely linked to community utilisation activities, where mangrove diversity and species dominance support various local livelihood practices. There are seven activities carried out within the mangrove forest area. Tree cutting, bark stripping, and waste disposal in coastal areas are activities that directly have detrimental impacts on mangrove forests. These findings highlight both the ecological significance of mangrove species in the region and the high level of community dependence on mangrove resources, emphasising the need for sustainable management strategies to maintain ecosystem integrity while supporting local livelihoods.